THE ROLE OF INFLUENCERS IN INCREASING GEN Z'S POLITICAL EXPRESSION - R. Yogie Prawira (AKSELERASI: Jurnal Ilmiah Nasional, 2024)
This study aims to analyze the strategic role of social media influencers in enhancing the political expression of Generation Z (Gen Z). As digital natives, Gen Z tends to avoid conventional political bureaucracy and turn to digital platforms to voice their views. The research method used was a qualitative descriptive. The results reveal five crucial roles of influencers in the digital political ecosystem: 1) as interpreters of complex issues, simplifying policies through creative visuals; 2) facilitators of interactive discussion spaces that democratize opinion; 3) shapers of opinions and trends that validate political attitudes; 4) drivers of participation in action, mobilizing movements from online to offline; and 5) builders of community and social solidarity based on digital philanthropy. This study concludes that influencers have emerged as new, effective agents of political socialization, transforming traditional apathy into active and critical political expression, strengthening social cohesion among the younger generation in modern democracies.